Analysis of biofilms formation by Cronobacter sp. during growth in infant formula milk - Aishah Faiqah Mohd Yusof,; Pranesha Prabhakaran,; Nur Diyana Azli,; Norrakiah Abdullah Sani,; Wan Syaidatul Aqma, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Pacifier nipples are in permanent contact with saliva and with the oral microflora therefore, act as a favoured site for the growth of biofilms. This research was conducted to identify the bacterial biofilms that has been found on the pacifiers that collected from local child nursery and to analyse the formation of biofilms by Cronobacter sp. during growth in infant formula milk. Pacifiers collected were analysed to obtain colony forming unit (CFU) and isolated bacteria were identified using several biochemical tests according to Bergey’s Manual. Biofilm assay of three Cronobacter sp. were conducted using 24 wells microtiter plate and stained with 1% of crystal violet solution at different time interval: 6, 12, 18 and 24 h. The hydrophobicity of the bacterial cell suspension was evaluated using bacterial adhesion to hydrocarbons (BATH) method. Extracellular polymeric substances (EPS) analysis was done to identify percentage of carbohydrate and protein content by using phenol sulphuric acid method and Bradford method, respectively. The results obtained showed that the normal microflora bacteria were the most abundant microorganisms that were found on the pacifier with the main genus isolated was Staphylococcus sp., Enterobacteriaceae sp. and Clostridium sp. Based on biofilm and EPS analysis, Cronobacter sakazakii formed a strong biofilms after 18 h, with carbohydrate was identified as main component of EPS.